KEABSAHAN PERJANJIAN PINJAM-PAKAI ATAS BENDA YANG DIJAMINKAN PADA BAITUL MAAL WA TAMWIL - Nur Baiti (JOURNAL SAINS STUDENT RESEARCH, 2024)
A loan-to-use agreement with the object of the agreement being a pledged collateral object, which is carried out by BMT PAS as the party receiving the pledge as well as the party lending the pledged collateral object with MT acting as the party giving the pledge and the party receiving the loan of the pledged object, raises two questions, namely how valid it is. loan-to-use agreement for collateral objects and how the legal protection is for BMT PAS if the object lent is damaged or lost. This research is normative juridical research using a research approach, namely a conceptual approach, the results of which are analyzed using qualitative descriptive analysis. The results of this research regarding the validity of the loan-to-use agreement, there are two legal opinions, namely: first, that the loan-to-use agreement is a form of granting permission to use the pledged collateral, the basis is the opinion of the Hanafiyyah Ulama, Syafi'iyyah Ulama and Hanabilah Ulama, and the agreement has fulfilled the elements of a valid contract. Meanwhile, the second opinion comes from the Malikiyyah Ulama which is in line with the Civil Code, that the pledgor cannot use the pawned object at all, and the agreement does not meet the subjective requirements for the element of authority and the objective requirements for the object of the agreement, so that the loan-to-use agreement is invalid. Legal protection for BMT PAS also produces two opinions, namely according to the opinion of the three Ulama and according to the Civil Code.